2010
DOI: 10.1109/led.2010.2052586
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Silicide Contact Technology With Dual Near-Band-Edge Barrier Heights and Integration in CMOS FinFETs With Single Mask

Abstract: This letter reports the demonstration of a nickelsilicide contact technology that achieves dual near-band-edge barrier heights (i.e., a low electron barrier height Φ n B for n-FETs and a low hole barrier height Φ p B for p-FETs) using just one additional masking and two ion-implant steps. Independent and effective tuning of contact resistance R C is achieved in both p-and n-FinFETs. The compensation effect of aluminum and sulfur implants is studied for the first time and exploited for process simplification. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…3 shows the depth profiles of S and C in the metal/semiconductor structure. It has been reported that segregated S at the NiSi/Si interface is the key factor to tune Φ n B [9]- [14]. S is found to segregate at the NiSi/Si interface for both samples.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…3 shows the depth profiles of S and C in the metal/semiconductor structure. It has been reported that segregated S at the NiSi/Si interface is the key factor to tune Φ n B [9]- [14]. S is found to segregate at the NiSi/Si interface for both samples.…”
Section: Resultsmentioning
confidence: 75%
“…Furthermore, the addition of carbon (C) after PAI also enhances the thermal stability of NiSi and removes the end-ofrange (EOR) defects in amorphized Si [7], [8]. Manuscript On the other hand, it has been reported that introduction of sulfur (S) at the NiSi/n + Si interface can reduce the effective SBH or Φ n B to ∼0.1 eV [9]- [14]. S could act as a dopant to increase the thermionic field emission and tunneling current [15].…”
Section: Introductionmentioning
confidence: 99%
“…[77] Al and S implantation before NiSi formation to achieve near-bandedge barrier height for PMOS and NMOS, respectively, has been reported for FinFETs. [78] In other studies, PMOS received both Al and S implants, with Al doping level lower than S, while NMOS received only an Al implant, using one additional mask, which allows simpler CMOS process. A NiAl alloy was also demonstrated on NMOS FinFETs, forming Ni 2 AlSi.…”
Section: Nisi Formation On Finfetsmentioning
confidence: 99%